2022
DOI: 10.1155/2022/2642551
|View full text |Cite
|
Sign up to set email alerts
|

Bile Reflux Gastritis: Insights into Pathogenesis, Relevant Factors, Carcinomatous Risk, Diagnosis, and Management

Abstract: Bile reflux gastritis (BRG), a kind of gastrointestinal disorder in clinical practice, is characterized by regurgitation and inflammation. However, lack of guidelines leads to simple cognition and even ignorance of this disease for clinicians. Primarily, making the pathogenesis of BRG clear contributes to a correct and general understanding of this disease for physicians. Next, although recently there has been an increasing awareness among researchers in terms of the relevant factors for BRG, further studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
0
9
0
7
Order By: Relevance
“…Alkaline bile neutralizes the acidity of the stomach and turns it into a breeding ground for bacteria. Furthermore, bile acids and lysolecithin dissolve the fatty protective barrier of the gastric mucosa and expose it to hydrochloric acid, leading to gastritis [ 2 , 4 - 5 ]. It typically manifests as abdominal pain, dyspepsia, nausea, bilious vomiting, or heartburn [ 1 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alkaline bile neutralizes the acidity of the stomach and turns it into a breeding ground for bacteria. Furthermore, bile acids and lysolecithin dissolve the fatty protective barrier of the gastric mucosa and expose it to hydrochloric acid, leading to gastritis [ 2 , 4 - 5 ]. It typically manifests as abdominal pain, dyspepsia, nausea, bilious vomiting, or heartburn [ 1 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, duodenal reflux liquids contain gut microbiome that can result in the imbalance of microbial flora in the stomach [ 32 ]. Moreover, the rise in the pH value due to alkaline bile creates a favorable environment for bacterial multiplication, further aggravating gastric inflammation [ 33 ]. In this patient, the probability of developing a gastric perforation could be facilitated by the administration of nonsteroidal anti-inflammatory drugs (NSAIDs), as reported in the dog’s anamnesis.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration and duration of bile exposure are positively correlated with the incidence of GC and may lead to the recurrence of gastric stump cancer ( 73 ). A clinical study from China also showed that the independent risk factors of GC lesions included bile reflux grade, patient age, diet habits, and GC family history ( 73 ).…”
Section: Occurrence and Development Factorsmentioning
confidence: 99%
“…The concentration and duration of bile exposure are positively correlated with the incidence of GC and may lead to the recurrence of gastric stump cancer ( 73 ). A clinical study from China also showed that the independent risk factors of GC lesions included bile reflux grade, patient age, diet habits, and GC family history ( 73 ). Currently, the oncogenic mechanism of bile reflux is not fully understood, but it may be connected to the increased formation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) induced by bile acid exposure that result in DNA damage and mutation of the oncogene p53 ( 74 ).…”
Section: Occurrence and Development Factorsmentioning
confidence: 99%